Integración de tecnologías emergentes en la gestión de proyectos integradores en la Carrera de Sistemas de Información. - Ciza Ciza, Andy Javier (2024)
The integration of emerging technologies in integrative projects has proven to be essential to maintain the relevance and effectiveness of education in the Information Systems career. The same ones that allow the correct preparation of integrative projects, because they are being used and perceived in the management of integrative projects in the aforementioned career. This research will use qualitative methodology to obtain a complete analysis of the situation that is happening at the moment. The target population includes the director and coordinator of the Systems degree, whose experiences in project management constitute the main sample. Obtaining data through semi-structured interviews that explore the opinions and experiences of the interviewees, to objectively measure the impact of emerging technologies within the project management of the information systems career. On the other hand, it highlights the need to constantly adapt integrative projects to reflect the demands of the labor market and provide students with practical experience in technologies and highlights the importance of this integration to allow students to apply practical knowledge and keep up to date. constant of integrative projects.